Pronunciation strategies used by EFL students - Rita Hermida (ACCENTIA: Journal of English Language and Education, 2022)
This study analyzes the students’ pronunciation strategies used to learn pronunciation. The study used a qualitative method to investigate the dominant strategies used by student in learning pronunciation.  The main data was taken by distributed the questionnaires to the students in order to get the main point about the strategies they used. Besides, unstructed interview was also used to support the main data.  The research was carried out at an Islamic Boarding School in Aceh Besar Senior High Level.  The findings show that The first strategy is input/practice, as concrete experience, concrete experience refers to when students engage in activities such as searching, listening, or watching, and repeating sounds, or practicing the sound to improve pronunciation.